2011
DOI: 10.1186/1471-2350-12-142
|View full text |Cite
|
Sign up to set email alerts
|

IL13genetic polymorphisms, smoking, and eczema in women: a case-control study in Japan

Abstract: BackgroundSeveral genetic association studies have examined the relationships between single nucleotide polymorphisms (SNPs) in the IL13 gene and eczema, and have provided contradictory results. We investigated the relationship between the IL13 SNPs rs1800925 and rs20541 and the risk of eczema in Japanese young adult women.MethodsIncluded were 188 cases who met the criteria of the International Study of Asthma and Allergies in Childhood (ISAAC) for eczema. Control subjects were 1,082 women without eczema accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[26][27][28] This antiinflammatory cytokine plays a pivotal role in the pathogenesis of several diseases such as asthma, autoimmune thyroid disease, RA, SLE, eczema, pulmonary disease and atopy through hypersensitivity, IgE synthesis, mast cell hyperplasia, tissue remodeling and fibrosis. [29][30][31][32][33][34] The gene encoding for IL-13 is located on chromosome 5q31-33. Recent research has revealed that this location is one of the vulnerable regions for the susceptibility of asthma or atopic dermatitis, which suggests that IL-13 could have an association with autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] This antiinflammatory cytokine plays a pivotal role in the pathogenesis of several diseases such as asthma, autoimmune thyroid disease, RA, SLE, eczema, pulmonary disease and atopy through hypersensitivity, IgE synthesis, mast cell hyperplasia, tissue remodeling and fibrosis. [29][30][31][32][33][34] The gene encoding for IL-13 is located on chromosome 5q31-33. Recent research has revealed that this location is one of the vulnerable regions for the susceptibility of asthma or atopic dermatitis, which suggests that IL-13 could have an association with autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%